Soccer skills norm for cadets of the Philippine Military Academy - Cabreza, Eminiano A. ([S.l. s.n.], 1974)
This study aimed to construct norms for four major soccer skill tests used for the cadets of the Philippine Military Academy. The skill tests are: the soccer dribble test, the heading test, the Mcdonald volleying soccer test and the place kick for distance test. It also determined the average scores (median and mean) of the cadets in the aforementioned skill tests.
Thesis (M.A.T.)--University of the Philippines, Quezon City.
Keywords: Soccer -- Training. -- Philippines; Philippine Military Academy -- Cadets